(3JhVjM GdeTJHgs - (3eMeO Hf YHO Gddg (B((3CHj HcQ(B) (3Hf eMeO GHf CMeO Hf eLGgO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf , (B842 (3g` s; (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3jHOC ef Chd GdcJGH s
(3BNQgG (B:s
(3jfJgi Edi GSe (B: (3GdMLQi , ef CKfGA MQa GdMGA s
(3ef fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B47 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs